2018
DOI: 10.3390/toxins10040161
|View full text |Cite
|
Sign up to set email alerts
|

Analogs of the Scorpion Venom Peptide Stigmurin: Structural Assessment, Toxicity, and Increased Antimicrobial Activity

Abstract: Scorpion venom is a rich source of biologically active components and various peptides with high-potential therapeutic use that have been characterized for their antimicrobial and antiproliferative activities. Stigmurin is a peptide identified from the Tityus stigmurus venom gland with high antibacterial and antiproliferative activities and low toxicity. Amino acid substitutions in peptides without a disulfide bridge sequence have been made with the aim of reducing their toxicity and increasing their biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Various antimicrobial peptides from aquatic animals have been isolated and tested against epimatigote forms of T. cruzi ; however, they did not show antiparasitic activity for these strains [28], different from the analog peptides StigA25 and StigA31, which demonstrated a high inhibition rate. Similar activity was also shown for other analog peptides from the scorpion peptide Stigmurin [15] and various analog peptides from scorpion venom with significant activity against trypanosomatides [29]. When tested in trypomastigote forms of the T. cruzi and Y strains we observed the same pattern for epimastigote, with the analogs peptides showing higher activity than the native peptide Stigmurin.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Various antimicrobial peptides from aquatic animals have been isolated and tested against epimatigote forms of T. cruzi ; however, they did not show antiparasitic activity for these strains [28], different from the analog peptides StigA25 and StigA31, which demonstrated a high inhibition rate. Similar activity was also shown for other analog peptides from the scorpion peptide Stigmurin [15] and various analog peptides from scorpion venom with significant activity against trypanosomatides [29]. When tested in trypomastigote forms of the T. cruzi and Y strains we observed the same pattern for epimastigote, with the analogs peptides showing higher activity than the native peptide Stigmurin.…”
Section: Discussionsupporting
confidence: 81%
“…Regarding the antiparasitic activity, the three tested peptides inhibited the epimastigote forms of the T. cruzi Y strain. No significant difference was observed between the inhibition caused by the analog peptides; though when compared with the native peptide Stigmurin in an earlier study, both analog peptides showed higher antiparasitic activity [15]. Various antimicrobial peptides from aquatic animals have been isolated and tested against epimatigote forms of T. cruzi ; however, they did not show antiparasitic activity for these strains [28], different from the analog peptides StigA25 and StigA31, which demonstrated a high inhibition rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent studies focus on the evaluation of potential new drugs in the context of trypanosomatid infections. Thus, the mechanism of the antigenic variation of T. brucei seems to be an interesting target for the search for potential new antiparasitic molecules [43,44]. Consequently, understanding the mechanism of VSG release and all the involved molecules represents an important strategy for the development of new drugs against infections caused by T. brucei.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the net positive charge of these analogues facilitates their interaction with the target cell membranes [43]. Two analogs of the peptide stigmurin from the Tityus stigmurus venom gland named StigA6 and StigA16 revealed increased antimicrobial activity and less toxicity on the normal cell line, while retaining the activity of the native peptide on cancer cells [44].…”
Section: Antimicrobial Agents From Scorpionsmentioning
confidence: 99%